Effect of Metronidazole on the Intestinal Microflora of the American Cockroach, Periplaneta americana L - Bracke, J. W. (1978)
The effect of feeding to cockroaches the antimicrobial agent metronidazole, which acts specifically against anaerobes, was assessed by light and scanning electron microscopy, bacteriological examination, and methane formation. Types of organisms and total numbers were greatly reduced from controls. The health of mature adults was unaffected, but stunting occurred in subadult animals maintained on the antibiotic from hatching. The intracellular bacteria of the fat body were not affected by the drug. The results are discussed with respect to a proposed microbe-host extracellular symbiosis.